Atendimento antirrábico humano pós-exposição: proposta de intervenção e estudo da percepção do comportamento de cães e gatos envolvidos nos agravos - Grisólio, Ana Paula Rodomilli [UNESP] (2014)
In Brazil, although urban rabies is controlled in most states, the costs with human post-exposure prophylactic treatment are very high. This concerns particularly the Ministry of Health. Therefore, this study aimed propose strategic measures to improve the medical service to people involved with animals attacks, in Jaboticabal, São Paulo, reducing the number of rabies post-exposure treatments. Were used as tools, two new records, the record of Reference for Animal Aggression and the record of Zoossanitaries Visits. Home visits with the purpose of assisting in investigations of reported cases and analyze the behavior of the animals involved were also performed. Between the months of September 2012 and August 2013, 226 cases of injuries were reported and made 185 visits. The species of greatest interest in aggravations was the canine (86%), followed by feline (11,5%) and other species such as rodents, primates and cattle (2.5%). Dogs and cats observed during the 10 days after the accident, 65,5 % were domiciled, 57,5% vaccinated against rabies and 88% remained healthy until the end of the period. The anatomic areas most affected were hands (40,5%) and lower limbs (34%). In total 316 doses of rabies vaccine were used. Based on the data of the chips and analysis of animal health visits, it was found that 248 vaccines could have been dispensed, which represents a saving of over $3.000,00, only considered the cost immunobiological. If were computed all direct and indirect expenses, this number could triple. The inclusion of content analysis occurred, to interpret the descriptions given by the victims about how the injuries, allowed a more accurate assessment of the circumstances involved and the real reasons that led to aggression by animals. The project involved the public and the employees of the Health Department of the Municipality studied, seeking greater integration of medical and veterinary ...